2012
DOI: 10.1007/s00396-012-2613-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed layers of DPPC and a linear poly(ethylene glycol)-b-hyperbranched poly(glycerol) block copolymer having a cholesteryl end group

Abstract: Interactions of the phospholipid 1,2-dipalmitoylsn-glycero-3-phosphocholine (DPPC) with the amphiphilic diblock copolymer Ch-lPEG 30 -b-hbPG 24 (ChP) are studied at the air-water interface by surface pressure-mean molecular area (π-mmA) measurements of mixed Langmuir films and adsorption measurements of ChP to the air-water interface covered with DPPC monolayers at different initial surface pressure values π 0 . ChP is composed of a single hydrophobic cholesteryl (Ch) moiety covalently bound to a diblock copol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…Previous detailed studies of the molecular interactions between these block copolymers and phospholipids in Langmuir monolayers suggested their strong affinity. [23][24][25][26] In interactions with GUV phospholipid bilayers we observed clear differences assumed to arise from the different copolymer conformations in water. Moreover, it was found that the studied copolymers are able to cross articial and natural phospholipid membranes.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous detailed studies of the molecular interactions between these block copolymers and phospholipids in Langmuir monolayers suggested their strong affinity. [23][24][25][26] In interactions with GUV phospholipid bilayers we observed clear differences assumed to arise from the different copolymer conformations in water. Moreover, it was found that the studied copolymers are able to cross articial and natural phospholipid membranes.…”
Section: Introductionmentioning
confidence: 82%
“…Cholesterol, by itself a weak amphiphile and a component of natural membranes, is known for its strong interaction with phospholipids 34 and acts as an anchor in phospholipid layers. 26,29 The PPO-chain, as the weak hydrophobic middle block, is very exible and can interact with phospholipid layers in different ways. 23,24 Furthermore, the different architectures of the hydrophilic blocks, linear or hyperbranched, are expected to show different spatial molecular conformations in dilute aqueous solutions.…”
Section: Polymer Characterisationmentioning
confidence: 99%
“…9b). 25,26,55 Small membrane pieces are released inside and outside the bilayer, but nevertheless these GUVs remained stable for more than 24 h (see Fig.…”
Section: Polymer Interaction With Giant Unilamellar Vesicles (Guvs)mentioning
confidence: 99%
“…Furthermore, the LE/LC transition has much in common with the liquid-crystalline to gel phase transition in bilayer systems. [24][25][26] Monolayer experiments were combined with epi-fluorescence microscopy, and interactions of the fluorescent labelled block copolymer with phospholipid bilayers were studied by confocal laser scanning microscopy (CLSM) employing giant unilamellar vesicles (GUVs). 1,14,15 Cholesterol exhibits a so-called ''condensing effect'' on liquid-crystalline bilayers, 1,7,10 which can be understood as the induction of an intermediate state of the lipid acyl chains between the ordered and the liquid crystalline state.…”
Section: Introductionmentioning
confidence: 99%
“…There exist numerous lipid bilayer-forming agents. Dipalmitoylphosphatidylcholine (DPPC) is a typical example; on the one hand, it is extensively studied experimentally [ 14 , 21 , 22 , 23 , 24 , 25 ], while, on the other hand, it is well-covered in force-field support [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%